2020
DOI: 10.1186/s12887-020-1947-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and metabolic characterization of patients with short-chain enoyl-CoA hydratase(ECHS1) deficiency: two case reports and the review of the literature

Abstract: Background: Short-chain enoyl-CoA hydratase (SCEH or ECHS1) deficiency is a rare congenital metabolic disorder caused by biallelic mutations in the ECHS gene. Clinical phenotype includes severe developmental delay, regression, dystonia, seizures, elevated lactate, and brain MRI abnormalities consistent with Leigh syndrome (LS). SCEH is most notably involved in valine catabolism. There is no effective treatment for the disease, patients may respond to dietary restriction of valine and supplementation of N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In the valine pathway, it is originated from acryloyl-CoA, but the exact mechanism is not clear. 23DH2MB abnormalities were also identified in a few Leigh syndrome patients with ECHS1 mutations ( Peters et al, 2014 ; Yang and Yu, 2020 ). There was only 2 reported patient with an HIBCH mutation with elevated urinary 23DH2MB excretion ( Ferdinandusse et al, 2013 ; Marti-Sanchez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 91%
“…In the valine pathway, it is originated from acryloyl-CoA, but the exact mechanism is not clear. 23DH2MB abnormalities were also identified in a few Leigh syndrome patients with ECHS1 mutations ( Peters et al, 2014 ; Yang and Yu, 2020 ). There was only 2 reported patient with an HIBCH mutation with elevated urinary 23DH2MB excretion ( Ferdinandusse et al, 2013 ; Marti-Sanchez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 91%
“…To date, 63 SCEH patients are described, all presenting between 0 and 18 years of age. 2,4,[26][27][28][29][30][31][32][33][34][35]8,36,[10][11][12][13]22,24,25,59 Three distinct clinical phenotypes are reported: LS (79%), paroxysmal dystonia (10%), and fatal neonatal lactic acidosis (11%) ( Table S1). Kaplan-Meier survival curves showed that half of the patients died before 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite was found in 75% of HIBCH cases in our study and in previous series. 4,9,26,27,40,41,45,54 Forty-three different ECHS1 mutations in 63 SCEH patients from 54 families have been described 2,4,[26][27][28][29][30][31][32][33][34][35]8,36,[10][11][12][13]22,24,25,59 ( Figure S2). Overall, 73% of the variants were present exclusively in one or two alleles, confirming the wide genetic heterogeneity of ECHS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients present with developmental delay, regression, dystonia, feeding difficulties, cardiomyopathy, and brain MRI changes consistent with Leigh syndrome. Since Sharpe et al, reviewed the mutational, clinical, and biochemical spectrum of 42 patients from 33 families with ECHS1 disease, an additional nine new cases have been reported, none of which are due to synonymous mutations (Aretini et al, 2018;Carlston, Ferdinandusse, Hobert, Mao, & Longo, 2019;Pajares et al, 2020;Ronchi et al, 2020;Sharpe & McKenzie, 2018;Uchino et al, 2019;Wu et al, 2020;Yang & Yu, 2020). Here we report clinical, biochemical, molecular, and functional data on four patients from two unrelated families, presenting with two novel mutations in ECHS1.…”
Section: Introductionmentioning
confidence: 99%